Towards Policy Strategies for Managing Vertebrate Pests in Arid and Semi-arid Regions of India: REVIEW PAPER - Mani Chellappan; Ranjith MT; Vipin Chaudhary (Annals of Arid Zone, 2025)
Vertebrate pest conflict has become a significant production constraint in India’s arid and semi-arid agro-ecosystems, where small and rainfed farms are highly vulnerable to crop depredation and resource competition with wildlife. Species such as wild boar, nilgai, Indian peafowl, and rodents frequently cause severe yield losses ranging from 15% to 50% in drought-prone farming areas. Habitat fragmentation, expansion of irrigated pockets in drylands, and climate-driven scarcity of forage and water have intensified wildlife movement into cultivated fields, particularly in states like Rajasthan, Gujarat, and dry zones of Karnataka and Madhya Pradesh. Despite increasing damage reports, mitigation remains limited due to procedural delays, fragmented responsibilities between forest and agriculture institutions, and inadequate access to validated non-lethal deterrents. This review synthesizes emerging ecological trends, regional vulnerability patterns, and socioeconomic impacts of vertebrate pests within arid and semi-arid regions. The paper outlines a farmer-supportive Vertebrate Pest Management Policy Framework that emphasizes rapid-response legal mechanisms, insurance-linked compensation, commercialization of eco-friendly repellents and bio-fencing technologies, and community-managed deterrent systems. Enhancing institutional coordination, field-level adoption of proven technologies, and dryland-specific planning approaches is crucial for safeguarding livelihoods and strengthening climate-resilient agriculture in India’s arid landscapes.